AN EMPIRICAL STUDY OF ISLAMIC MICROFINANCE PERFORMANCE FOR POOR FAMILY: MAQASHID AL-SHARIA PERSPECTIVE - Aas Nurasyiah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
This research motivated by Islamic Microfinance performance measurement which still adopting on the performance measurement of microfinance in general that limited to the measurement of material. Therefore, efforts urgently needed to introduce more holistic measurement in assessing the performance of Islamic Microfinance based on tawheed principle. Thus, this study aims to measure the performance of Islamic Microfinance institutions based on Maqashid Al-Sharia. This research method uses quantitative approach with descriptive quantitative research design, which measures variables based on certain indicators. The location of the research is KOPMU-DT as one of the Islamic Microfinance institutions located in Bandung. The population of the study was the members KOPMU-DT wide-spread, among thousand people, but the withdrawal sample technique uses non-probability sampling with a sample of 100 members, based on the criteria that have been determined. Based on the research result, generally the members of KOPMU-DT increased living standards of the family economy and the performance of running micro-businesses. In Maqashid Al-Sharia perspective, the members experience a change in the principles of Ad-Din Al-Aql, A-nafs, An-Nasl and Al-Maal. However, among five principles, Al-Aql increases lower than other principles. In the future, to improve the performance of Islamic Microfinance, especially in KOPMU-DT, needs technical effort / business of accompaniment improvement to develop entrepreneurship from members. In addition, needs to give appreciation to the consistent members and disciplined in order to refund to add its financing to stimulate the operating business, without losing spiritual accompaniment to strengthen the achievement of Maqashid Al-Sharia of the empowerment members of Islamic Microfinance institution.Keywords: Islamic Microfinance, Maqashid Al-Sharia, Performance